DESIGNING A MODEL OF RESEARCH PAPER WRITING INSTRUCTIONAL MATERIALS FOR ACADEMIC WRITING COURSE: TEXTBOOK EVALUATION - Ghufron, M. Ali; Saleh, Mursid (Language Circle: Journal of Language and Literature, 2016)
This study attempted to evaluate an academic writing textbook used in English Education Study Program of Language and Art Education Faculty of IKIP PGRI Bojonegoro, East Java, Indonesia. The fourth edition of a book entitled âWriting Academic Englishâ written by Oshima and Hogue was critically evaluated based on two major points, namely general attributes of the textbook and the learning-teaching contents of the textbook. The general attributes of the textbook cover the book in relation to syllabus and curriculum, the methodology, the bookâs suitability to learners, physical and utilitarian attributes, and efficient outlay of supplementary materials; and the learning-teaching content of the textbook covers general elements (move of the tasks, tasksâ objectives, etc.), academic writing (specified on research paper writing), vocabulary, grammar, and exercises. The questionnaires developed to evaluate the textbook were adapted from textbook evaluation checklist developed by Mukundan, Nimehchisalem, and Hajimohammadi (2011). The results indicate that the lecturers and students were not really satisfied with the book since it does not represent the studentsâ needs and curriculum (the curriculum of English Education Study Program of IKIP PGRI Bojonegoro mandated to teach research paper writing for Writing IV course). The materials provided there are not specified to research paper writing. However, the textbook is very good in some points such as the methodology, physical and utilitarian attributes, layout of the book, general elements (move of the tasks, tasksâ objectives, etc.), academic writing (from paragraph writing to various essays writing), vocabulary, grammar, and exercises in the area.